Cashless Payments and Banking Performances: A Study of Local Commercial Banks in Malaysia - Lu, Ming Pey (UUM, 2021)
Malaysia is on its way to cashless society as well as moving towards IR4.0. This study investigates the impacts of cashless payment channels (ATMs, internet banking and mobile banking) and instruments (credit card, debit card, charge card and e-money) on banking performances for eight local commercial banks in Malaysia over the period of 2005 to 2018. The findings show that cashless payments are positively related to ROA and ROE of bank except e-money. Furthermore, the study demonstrates that the cashless payments has improved the cost-to-income ratio of bank except ATMs. Meanwhile, this study disaggregates the sample into subperiod analysis to further examine the transition effect of the cashless payments on banks’ performances. The findings show that the significant effects of cashless payments on ROA and ROE are mainly driven by the usage of cashless payments in first wave (2005-2009). There is no progressive impact found for second (2010-2014) and third wave (2015-2018) of progressive development. Also, the findings reveal that the progressive development of cashless payment does not significantly moderate the relationship between cashless payments and banks’ efficiency performance. This suggest that cashless payments do not add values to banks’ performances in the long run. In brief, this study has contributed in examine the impacts of cashless payments on banks’ performances for local commercial banks in Malaysia and highlighted the progressive impact of cashless payments on banks’ performances.